The impacts of the COVID-19 pandemic crisis on rural entrepreneurs - Muhamad Asri Abdullah Kamar,; Mohamad Azal Fikry Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Rural entrepreneurs are significant business groups, being the contributors to the nation’s economy. They are the creators of job opportunities, but they are facing great challenges during the COVID-19 pandemic crisis. The objective of this research is to explore the impact of the pandemic on rural entrepreneurs. The current research was carried out at the Rural Community Centre (RCC) of Kg. Jelintoh, Gopeng, Perak, Malaysia. Being the most active RCC in conducting entrepreneurship programmes in 2019, that centre was chosen for this study. This exploration research utilised qualitative approach which involved an in-depth interview by using a semi-structured interview format with seven rural entrepreneurs. They were selected through a purposive sampling from the list of rural entrepreneurs. The data were analysed using a thematic analysis method. The results revealed two main themes of the impacts. The first theme was business operation which includes operation disruption, decrease in demand, shortage of logistic supply, and operation closure. The second theme involves business finance that consists of cash flow problems, unexpected increase in production cost, and access to economic stimulus package. The findings from this research provide good inputs to relevant agencies in assisting the rural entrepreneurs to resume their businesses. It is recommended that all types of rural businesses to be allowed to run their normal operations, ensure the smoothness of logistics supply, being offered with financial aids, reduce the production cost, and create an easy-access entry to economic stimulus package.